1999
DOI: 10.1038/sj.bmt.1701924
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of molecular evidence for tumour in PBPC harvests from patients with high risk Ewing tumours

Abstract: Reverse transcriptase polymerase chain reaction (RT-PCR) was applied to evaluate the frequency of tumour cells in PBPC products from 15 high risk Ewing tumour (ET) patients who were treated according to EICESS 92 with high-dose chemotherapy (HDC) and stem cell rescue. Initial tumour cell contamination of the bone marrow (BM) detected by light microscopy was found in five and by RT-PCR in eight cases. RT-PCR was performed on each PBPC sample repeatedly at a sensitivity comparable to 20-100 highly EWS-Fli1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Two other studies have also reported a high incidence of contamination by tumour cells, occurring in either marrow or PBSC grafts of all five patients in both studies (Toretsky et al, 1995;Leung et al, 1998). The incidence of tumour cell contamination of PBSC products in the present study (8%) is more consistent with the findings of three other studies which reported a proportion of patients with tumour cell contamination of PBSC samples of one out of 15 (6.7%), one out of nine (11.1%), and three out of 15 (20%), respectively (Fischmeister et al, 1999;Montanaro et al, 1999;Thomson et al, 1999). This important variability in incidence of tumour cell contamination in PBSC collections in previous reports might be due to different sensitivity and specificity of the techniques of detection, to different times of harvesting and to different disease status at the time of PBSC collection.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Two other studies have also reported a high incidence of contamination by tumour cells, occurring in either marrow or PBSC grafts of all five patients in both studies (Toretsky et al, 1995;Leung et al, 1998). The incidence of tumour cell contamination of PBSC products in the present study (8%) is more consistent with the findings of three other studies which reported a proportion of patients with tumour cell contamination of PBSC samples of one out of 15 (6.7%), one out of nine (11.1%), and three out of 15 (20%), respectively (Fischmeister et al, 1999;Montanaro et al, 1999;Thomson et al, 1999). This important variability in incidence of tumour cell contamination in PBSC collections in previous reports might be due to different sensitivity and specificity of the techniques of detection, to different times of harvesting and to different disease status at the time of PBSC collection.…”
Section: Discussionsupporting
confidence: 82%
“…In two other studies tumour cells in BM detected by RT -PCR were observed in two out of the three PBSC-positive patients tested and in three out of the three PBSC-positive patients tested but also in the only PBSC-negative patient, respectively (Toretsky et al, 1995;Leung et al, 1998). Interestingly, in the two series with a low incidence of tumour cell contamination of PBSC collection, no cases of BM micometastases at the time of PBSC collection were observed in the first and only one case in the second study (Fischmeister et al, 1999;Thomson et al, 1999). This observation might suggest that micrometastatic disease in BM should be sought for before collecting PBSC.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…19 We and others have previously studied tumor contamination in PBSC harvests from EFT patients and revealed a high incidence of contamination. [15][16][17][18][19] Toretsky et al 15 identified the chimeric transcript in the blood progenitor cell collections of all five of their EFT patients studied. Leung et al 16 studied five high-risk EFT patients and all were reverse transcription (RT)-PCR positive, either in marrow or blood grafts.…”
mentioning
confidence: 99%
“…At least one positive collection was identified in one out of nine and 10 out of 15 high-risk EFT patients. 17,18 In our previous study, tumor-contaminated harvests were detected by RT-PCR in all 11 patients in at least one of the collections. 19 In this study, we investigated tumor cell contamination in harvests from EFT patients prior and after CD34 þ selection by RT-PCR and flow cytometry (FC) analyses and studied primary tumor cells for mRNA expression of CD34 by RT-PCR.…”
mentioning
confidence: 99%